The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1413-81232004000100019
|View full text |Cite
|
Sign up to set email alerts
|

Postura sentada: a eficácia de um programa de educação para escolares

Abstract: This work had as aim the seat posture evaluation program from first-grade students in elementary school, in a public, private and municipal school, in Bauru. For that 71 students were evaluated (pre-test) about knowledges related to seat posture education after all it was given an education program about it, made by exposured class, proof techniques and feedback associated of an effort program supplied by trained professors and finally the revaluation (post-test) of participants knowledge. As a result: 1) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
42

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 9 publications
(8 reference statements)
0
17
0
42
Order By: Relevance
“…25 Educational and therapeutic experiences have shown that the practice of leisure and sport activities in physical education is fundamental to the acquisition of healthy postural habits.Moreover, the right position to study and carry school supplies functions as an adjunct to treatment.Although this study did not investigate the associated factors in the onset of pain, the improper use of backpacks is an improper postural habitwhich can promote postural change, 18 empowering a problem that is already installed, and increasing the chances of occurrence of LBP. [18][19] Accordingly, Basso et al 31 demonstrated a correlation between the inappropriate use of backpacks and postural changes, being this correlation potentiated in children who have mouth breathing predominance.Thus, appropriate monitoring with guidelines and serial evaluations of research on postural changes,are the key role in early diagnosis and treatment of children and adolescents. 13 The study findings highlight the need for efforts to prevent and reduce harmful behaviourwhichmay contribute to the development of postural deviations and changes that may cause or worsen cases of low back pain in adolescents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 Educational and therapeutic experiences have shown that the practice of leisure and sport activities in physical education is fundamental to the acquisition of healthy postural habits.Moreover, the right position to study and carry school supplies functions as an adjunct to treatment.Although this study did not investigate the associated factors in the onset of pain, the improper use of backpacks is an improper postural habitwhich can promote postural change, 18 empowering a problem that is already installed, and increasing the chances of occurrence of LBP. [18][19] Accordingly, Basso et al 31 demonstrated a correlation between the inappropriate use of backpacks and postural changes, being this correlation potentiated in children who have mouth breathing predominance.Thus, appropriate monitoring with guidelines and serial evaluations of research on postural changes,are the key role in early diagnosis and treatment of children and adolescents. 13 The study findings highlight the need for efforts to prevent and reduce harmful behaviourwhichmay contribute to the development of postural deviations and changes that may cause or worsen cases of low back pain in adolescents.…”
Section: Discussionmentioning
confidence: 98%
“…17 Importantly, most bad postural habits are established during growth and sexual maturation phases, respectively, in childhood and adolescence, causing postural changes, particularly lateral and anterior-posterior changes, which can also be related to sitting posture, either whenattending school or to watching TV. 18,19 The early correction of postural additions is essential, because it enables a better prognosis and treatment perspectives. 19 Moreover, serious low back pain is a public health problem, famously because of the different treatments used nowadays, studies on prevalence are an indispensable guide and manager of healthybehaviours in the statement of interventions to improve the general framework and decreased effects on employment and social activities, particularly in the school environment.Due to the fact of being vulnerable to experience wide variation in their growth and development, the adolescent becomes a target to strategies to reduce musculoskeletal disorders at this stage of life providing, thus, improved quality of life in adulthood.The aim of this study is to estimate the prevalence of low back pain among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Este pode contribuir para o surgimento de desgastes articulares, dos discos intervertebrais e tendões 15 , tendo ainda como resposta alterações circulatórias e metabólicas locais, tornandoas auto-perpetuantes. 18 A atividade do plantio de sementes em saquinhos, estando o adolescente sentado em um toquinho de madeira, promove um trabalho predominantemente estático de tronco, lombar, cervical, ombros e membros inferiores. Concomitantemente suportam a flexão e extensão de cotovelos sem apoio, ao mesmo tempo em que punhos e dedos executam um trabalho principalmente dinâmico.…”
Section: Discussionunclassified
“…Low back pain is a multifactorial disorder, with a diagnosis that is not always specific and is one of the most common musculoskeletal discomforts in adolescents and adults 1 . It reached 9.4% of the world population in 2010 2 , and for young population, studies presented variability in the estimated prevalence from 14% to 24% between 1991 and 2009 3 .…”
mentioning
confidence: 99%
“…The most frequent causes of low back pain in adolescents are usually related to the growing burden of inadequate support of school backpacks and prolonged sitting for long periods of time 1 . In addition, studies indicate that female and adolescents with inadequate lifestyle habits such as physical inactivity, sedentary behavior and overweight are the subgroups vulnerable to frequent low back complaints among adolescents 5,6 .…”
mentioning
confidence: 99%